A new comprehensive Classification Scheme for ECU Tendon Problems at the Wrist - Burda, Rastislav; Morochovič, Radoslav; Rudnay, Maroš; Špaková, Timea (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Based on a systematic review of the literature, description of previous classification schemes and new anatomical knowledge, a new comprehensive classification scheme for ECU tendon problems at the wrist is described.
Keywords: ECU-Sehne; Klassifikation für ECU-Probleme